1996
DOI: 10.1002/etc.5620151118
|View full text |Cite
|
Sign up to set email alerts
|

A survey of estrogenic activity in United Kingdom inland waters

Abstract: Abstract-Vitellogenin, a yolk-precursor protein normally found only in the blood plasma of sexually mature female teleosts and other egg-laying vertebrates, was used as an indicator of exposure of male rainbow trout (Oncorhynchus mykiss) to exogenous estrogens. Vitellogenin concentrations were measured using a specific radioimmunoassay for trout. Cages containing adult male trout were placed at the points of discharge and at varying distances downstream of treated sewage effluent outfalls into the River Lea (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
168
2
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 368 publications
(180 citation statements)
references
References 43 publications
7
168
2
3
Order By: Relevance
“…EE2 is only partially metabolized and incompletely removed by sewage treatment plants (STPs) and, therefore not surprisingly, has been detected in sewage treatment plant effluents in the low nanogram-per-liter range and occasionally in surface waters in the U.S., U.K., Canada, Brazil, Germany, and elsewhere (1-6). EE2 is not the only compound with estrogenic activity detected in STP effluents (7)(8)(9)(10)(11) although available data suggest natural and synthetic hormones represent the majority of the estrogenic activity in many effluents (12,13). Its relatively high relative biological activity (14)(15)(16)(17)(18) has led to a great deal of research on EE2, providing a far greater body of toxicity data than is available for most compounds.…”
Section: Introductionmentioning
confidence: 99%
“…EE2 is only partially metabolized and incompletely removed by sewage treatment plants (STPs) and, therefore not surprisingly, has been detected in sewage treatment plant effluents in the low nanogram-per-liter range and occasionally in surface waters in the U.S., U.K., Canada, Brazil, Germany, and elsewhere (1-6). EE2 is not the only compound with estrogenic activity detected in STP effluents (7)(8)(9)(10)(11) although available data suggest natural and synthetic hormones represent the majority of the estrogenic activity in many effluents (12,13). Its relatively high relative biological activity (14)(15)(16)(17)(18) has led to a great deal of research on EE2, providing a far greater body of toxicity data than is available for most compounds.…”
Section: Introductionmentioning
confidence: 99%
“…That step was achieved by Harries et al [3,4], who quite remarkably demonstrated that a significant length of one river in northern England (the River Aire) was strongly estrogenic. That particular river was known to contain very high concentrations of nonylphenol (NP) and related chemicals, which are degradation products of one group of nonionic surfactants.…”
Section: Answering the Important Challengesmentioning
confidence: 99%
“…It would be difficult to think of a more environmentally relevant parameter than reproduction when attempting 2084 All Supplemental Data may be found in the online version of this article. See Table S1 for the number of citations and rank of all the ''Top 100'' papers, which in this essay are references [3][4][5][6][7][9][10][11][12][13][14][15]19,20].…”
Section: Answering the Important Challengesmentioning
confidence: 99%
“…Additionally, fish are easy to work with and their endocrine systems are similar to that of higher vertebrates; moreover, studies have demonstrated that fish are suffering from the disturbance of EDCs in their habitats (Jobling et al 1998;Lye et al 1999). Therefore, most of the investigations on EDCs in the environment have focused on the aquatic system using fish as an experimental model animal (Harries et al 1996;Jobling et al 1998;Pait and Nelson 2003). Vitellogenin (Vtg) has been used as an effective biomarker to demonstrate estrogenic effects of estrogens or estrogenic compounds in aquatic environments (Sumpter and Jobling 1995;Kime et al 1999;Marin and Matozzo 2004).…”
Section: Introductionmentioning
confidence: 99%